2013
DOI: 10.1111/mmi.12358
|View full text |Cite
|
Sign up to set email alerts
|

Induced ectopic expression of HigB toxin in Mycobacterium tuberculosis results in growth inhibition, reduced abundance of a subset of mRNAs and cleavage of tmRNA

Abstract: In Mycobacterium tuberculosis, the genes Rv1954A–Rv1957 form an operon that includes Rv1955 and Rv1956 which encode the HigB toxin and the HigA antitoxin respectively. We are interested in the role and regulation of this operon, since toxin–antitoxin systems have been suggested to play a part in the formation of persister cells in mycobacteria. To investigate the function of the higBA locus, effects of toxin expression on mycobacterial growth and transcript levels were assessed in M. tuberculosis H37Rv wild ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 76 publications
3
41
0
Order By: Relevance
“…This is consistent with our previous results, in which we have shown that two other TA loci toxins in NTHi, VapC-1 and VapD, are active on free RNA in vitro [13], [23]. Other studies have found that induced ectopic expression of the HigB toxin in M. tuberculosis lead to growth arrest and cell death as well as cleavage of tmRNA and mRNA predominantly from genes regulated by the IdeR iron-dependent repressor and the zinc uptake repressor Zur [24]. However, the HigB cleavage sites identified in the M. tuberculosis tmRNA ssrA in that investigation were not particularly A-rich.…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with our previous results, in which we have shown that two other TA loci toxins in NTHi, VapC-1 and VapD, are active on free RNA in vitro [13], [23]. Other studies have found that induced ectopic expression of the HigB toxin in M. tuberculosis lead to growth arrest and cell death as well as cleavage of tmRNA and mRNA predominantly from genes regulated by the IdeR iron-dependent repressor and the zinc uptake repressor Zur [24]. However, the HigB cleavage sites identified in the M. tuberculosis tmRNA ssrA in that investigation were not particularly A-rich.…”
Section: Resultssupporting
confidence: 93%
“…We revealed an 87‐amino acid‐long conserved domain of a putative HigB‐like addiction module killer toxin ( e ‐value < 10 −10 ) (Schuessler et al . ). A 222‐amino acid‐long putative transcriptional regulator of the xenobiotic response element family, which might serve as an antitoxin protein, was found downstream and antisense to the toxin ( e ‐value < 10 −8 ).…”
Section: Resultsmentioning
confidence: 97%
“…Transcription of TAC is induced in host phagocytes and by several stresses relevant for M. tuberculosis , including DNA damage, heat shock, nutrient starvation, hypoxia and multidrug persistence1013. In addition, ectopic expression of the Mtb -HigB1 toxin severely inhibits M. tuberculosis , M. marinum , M. smegmatis and Escherichia coli growth131415, and affects the relative abundance of over 30 transcripts in M. tuberculosis 15.…”
mentioning
confidence: 99%